A generic monograph of the Hyacinthaceae subfamily Urgineoideae - Martínez-Azorín, Mario; Crespo, Manuel B.; Vargas, María Ángeles Alonso-; Pinter, Michael; Crouch, Neil R.; Dold, Anthony P.; Mucina, Ladislav; Pfosser, Martin; Wetschnig, Wolfgang (Phytotaxa, 2023)
Taxonomy and systematics and specifically the generic circumscription of the Hyacinthaceae subfamily Urgineoideae have been a matter of controversy in recent decades. Widely contrasting taxonomic treatments have been proposed, ranging from systems comprising only two genera (including a morphologically very variable Drimia covering nearly the whole subfamily) to about 20 genera based mainly on preliminary phylogenetic studies supporting recognition of traditionally accepted and morphologically distinct genera such as Litanthus, Schizobasis, Tenicroa, and Thuranthos. All previous studies covered only a limited diversity and distribution of the subfamily, precluding comprehensive insight into the evolution of the diversity within the subfamily. Based on detailed morphological, phylogenetic, and biogeographic studies in Urgineoideae, covering its whole distribution range and most of the currently known species, we present a new taxomic treatment of the subfamily focusing on the circumscription of genera. Our analyses revealed 31 phylogenetic lineages corroborating unique syndromes of morphological characters linked to well-defined biogeographic patterns. These lineages are interpreted as well-defined genera. An identification key to the genera is provided to facilitate further taxonomic work in Urgineoideae and morphological descriptions of the accepted genera are presented. Two new genera, Spirophyllos gen. nov. and Zulusia gen. nov., are described to accommodate newly revealed phylogenetic lineages from northwestern and southeastern Africa, respectively. Further, a complete list of taxa included in the accepted genera is presented, providing details on typification, and the 50 new combinations, and one new name required to appropriately accomodate taxa in the new taxonomic treatment.